A prospective 24 months follow-up of a three component press-fit prosthesis for hallux rigidus - Wassink, S; Burger, B J; Saragas, N P; Asunción Márquez, J; Trtik, L; Harlaar, J (Foot and ankle surgery, 2017)
BACKGROUND: The aim of this study was to evaluate the results following total first metatarsophalangeal (FMTP) joint replacement arthroplasty using a modular three component press fit prosthesis at two year follow up. METHODS: All patient data was collected in a prospective way in four study centres. Both preoperative and postoperative evaluation consisted of an assessment using the AOFAS-HMI score, visual analogue scale for pain, evaluation of the range of motion and patient satisfaction scores. Postoperative X-rays were reviewed for loosening and radiolucency up to two years. RESULTS: Fifty-five feet were available for analysis at 24 months. Two implants were removed during the study. Six more feet had additional surgery due to stiffness or malalignment. Postoperative AOFAS-HMI scores improved significantly by 32.4 points at two year follow-up (p<0.001). The visual analogue scale for pain improved significantly from 6.8 (std 1,6) preoperatively to 1.6 (std 1,9) postoperatively (p<0.0001). Mean dorsiflexion improved from 12.6 (std 10,1) degrees preoperatively to 31.2 (std 16,8) degrees postoperatively. Eighty-seven percent of patients were moderately to well satisfied with the end result. Eighteen prostheses showed radiolucency at 24 months. CONCLUSION: Implantation of a Metis® modular three component press fit prosthesis for the metatarsophalangeal joint in hallux rigidus shows significant improvement in AOFAS-HMI scores and a decrease in pain. Concerns remain with regard to early reoperation rate (14.5%) and long term survival of the implant. Future studies will have to address these aspects.
Keywords: dospělí; rozsah kloubních pohybů; artralgie; lidé; Prosthesis Design; prospektivní studie; Hallux Rigidus; Metatarsophalangeal Joint; hallux rigidus; Prosthesis Failure; artroplastiky kloubů; Aged, 80 and over; senioři; Range of Motion, Articular; Aged; Arthroplasty, Replacement; metatarzofalangeální kloub; lidé středního věku; senioři nad 80 let; Humans; Prospective Studies; Arthralgia; Follow-Up Studies; reoperace; Adult; Joint Prosthesis; Reoperation; selhání protézy; protézy kloubů; protézy - design; Middle Aged; následné studie